THE CORRELATION OF PROSPECTIVE TEACHERS’ TENDENCY OF CRITICAL THINKING AND THEIR CRITICAL THINKING SKILLS TOWARDS THEIR LEARNING OUTCOMES - Andayani, Yayuk (Unnes Science Education Journal, 2018)
This research employs Ex Facto approach to analyse the relation between prospective teachers’ critical thinking tendency (CTT) and their critical thinking skills (CTS) towards their learning outcome. The subject of this research the fifth semester students of Chemistry Education, Faculty of Teaching, Universitas Mataram academic year of 2017/2018. The research focuses on the teaching of Chemical Physics III subject to 40 people who are chosen under purposive sampling method. The variable of attribute is the use of project-based learning and CTT while the dependent variable is the CTS and students’ learning outcome. The data of CTT were obtained through questionnaires focusing on the matter while the students’ CTS and learning outcome were measured using essay tests. The analysis of the data utilizes Pearson correlation test. The result of the test showed significant relevance between CTT and CTS (rcount ; 0.341 > rtable ;0.312). Meanwhile, the total of CTT and learning outcome do not show significant coexistence (rcount ; 0.096 < rtable ;0.312), even though the indicator of open-mindedness displayed a significant coherence to learning outcome (rcount ; 0.449 > rtable ;0.312). Based on the result, to sum up, there is a significant relation between critical thinking tendency and critical thinking skills.